Adolescent Christian Discernment: Utilizing Richard Osmer’s Approach to Practical Theology to Help Young People Ages 14–18 Develop a Missional Practice - Smith, Jeremy D. (Journal of youth and theology, 2024)
Theoretically guided, evidence-based approaches to fostering Christian discernment among adolescents are limited. The context of mid-adolescence is one in which youth struggle to solidify identity. The discernment of vocational calling, career, and choice of college are among the major life decisions associated with this phase of life. As a component in Lubbock Christian University’s (lcu) Vocati: A Youth Theology Institute, this study utilized the four tasks described in Richard Osmer’s model of practical theology to engage youth in the crafting of a missional practice. Analysis of qualitative findings suggests the use of Osmer’s model may provide a framework for youth ministry programs to guide young people in the process of Christian discernment.